Frequency and determinants of domestic violence against Iranian women during the COVID-19 pandemic: a national cross-sectional survey - Arezoo Yari; Hosein Zahednezhad; Reza Ghanei Gheshlagh; Amanj Kurdi (BMC, 2021)
Abstract Introduction Domestic violence (social, legal, and health violence) is the most common type of violence against women. Due to factors such as the current quarantine, this type of violence has increased during the COVID-19 pandemic. The present study aimed to assess the frequency of domestic violence against women and identify the risk factor among Iranian women during the COVID-19 pandemic. Methods This online cross-sectional study was conducted on 203 Iranian women during May-June 2020. Data were collected using a domestic violence questionnaire, which measured three forms of violence, including physical, emotional, and sexual violence. A link of the questionnaire was distributed among anonymous subjects through social networking apps, such as WhatsApp and Telegram. The subjects were asked to complete the questionnaire based on their experiences during the COVID-19 pandemic. Data analysis was performed using descriptive statistics and a regression model. Results The descriptive results showed that the mean domestic violence against women in all the participants was 34.9 (SD: 17.28). In addition, 26.6% (n = 84), 26.1% (n = 53), and 21.2% of the subjects (n = 43) experienced high levels of physical, emotional, and sexual violence during the COVID-19 pandemic, respectively. The regression model also indicated that lower age, illiteracy/primary education, previous marriage(s), and unwanted/unwise marriage were the significant risk factors for domestic violence against women. Conclusion According to the results, domestic violence against women is common among Iranian women during the COVID-19 pandemic. Therefore, strategies are urgently needed to prevent and minimize such domestic violence, and such strategies could be adopted through providing educational opportunities, raising awareness, promoting wanted/wise marriage, and providing social support and rehabilitation opportunities to vulnerable social groups, especially vulnerable women.